Effect of combustion duration on the performance and emission characteristics of a spark ignition engine using hydrogen as a fuel - Yamin J.A.A.; Gupta H.N.; Bansal B.B.; Srivastava O.N. (My University, 2025)
The deteriorating quality of air due to exhaust emissions and the increasing number of motor vehicles in the world, is sending alarming waves throughout the world to try to do something to cut off or significantly reduce these emissions in order to save our planet. Scientists have found that hydrogen presents the best and unprecedented solution to this problem, for its superior combustion qualities and availability. This paper discusses analytically one aspect of combustion i.e. combustion duration and how it is affected by an engine's operating parameters like compression ratio, equivalence ratio, spark plug location, spark timing and engine speed, and how it affects an engine's performance parameters like brake specific fuel consumption, brake mean effective pressure, thermal efficiency, well as emission characteristics.